1995
DOI: 10.1074/jbc.270.9.4640
|View full text |Cite
|
Sign up to set email alerts
|

Sequence and Expression of a Candidate for the Human Secretor Blood Group α(1,2)Fucosyltransferase Gene (FUT2)

Abstract: We have used the human H blood group alpha(1,2)fucosyltransferase (FUT1) cDNA to screen chromosome 19 cosmid libraries in a search for the human Secretor (Se) blood group gene (FUT2). One cosmid has been isolated that contains two distinct segments that cross-hybridize with FUT1. We have assembled a 100-kilobase (kb) cosmid contig, localized to 19q13.3, encompassing FUT1 and the two FUT1-related sequences, termed Sec1 and Sec2, for Secretor candidate 1 and 2. Sec1 and Sec2 are separated by 12 kb and are 65.5 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
282
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 512 publications
(290 citation statements)
references
References 39 publications
7
282
0
1
Order By: Relevance
“…Characterization of the enzymatic activity indicates that A1,2FT expressed in COLO-205 cells is functionally different from HA1,2FT, and similar to the secretor-type activities [18]. Moreover, we found that in the Caco-2 and HT-29 cells, where SeA1,2FT specific activity is extremely low, Le b antigen expression is also very low or undetectable by immunofluorescence.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…Characterization of the enzymatic activity indicates that A1,2FT expressed in COLO-205 cells is functionally different from HA1,2FT, and similar to the secretor-type activities [18]. Moreover, we found that in the Caco-2 and HT-29 cells, where SeA1,2FT specific activity is extremely low, Le b antigen expression is also very low or undetectable by immunofluorescence.…”
Section: Discussionmentioning
confidence: 74%
“…SeA1,2FT was determined in a reaction mixture containing, in a final volume of 20 µl, 0.1 M Tris/HCl, pH 6.5, 0.5 mg/ml Triton X-100, 10 mM Fuc, 5 mM ATP, 360 µM donor GDP-[ 3 H]Fuc (specific radioactivity 25 mCi/mmol), 10 mM acceptor phenyl β-galactoside and 4.0 mg/ml cell protein, in the case of crude homogenate, or 0.2 mg/ml protein, in the case of the Golgi-enriched fraction. The reaction mixture lacks divalent cations, according to the procedure reported for genuine SeA1,2FT gene product [18]. Incubation was at 37°C for 90 min.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The human ␣(1,2)-Fuc-T gene family comprises FUT1 encoding for the H enzyme and FUT2 encoding for the human secretor ␣(1,2)-fucosyltransferase (9). FUT3-7 encode for ␣(1,3)-Fuc-Ts.…”
mentioning
confidence: 99%